Illusory responses across the Alzheimer's disease spectrum and Lewy body disease spectrum. (20th December 2022) - Shahid, Marian; Rawls, Ashley; Ramirez, Veronica; Ryman, Sephira; Santini, Veronica E; Yang, Laurice; Sha, Sharon; Hall, Jacob N; Montine, Thomas J.; Lin, Amy; Henderson, Victor; Cholerton, Brenna; et al.
Abstract: Background: Pareidolias are specific illusions of faces and objects perceived in formless visual stimuli. In studies using a noise pareidolia task in patients with clinical dementia, Dementia with Lewy Bodies patients report more illusory responses than Alzheimer's disease patients, which correlates with severity of visual hallucinations (Yokoi et al., 2014). However, it is unknown whether illusory responses occur in earlier stages of disease or in non‐hallucinating patients across the Lewy body disease (LBD) spectrum, such as Parkinson's Disease with and without cognitive impairment. Method: We studied the National Alzheimer's Coordinating Center Noise Pareidolia Task‐Short Form from the LBD Module in 300 participants from the Stanford Alzheimer's Disease Research Center and Pacific Udall Center who completed comprehensive motor and cognitive assessments with consensus diagnostic adjudication. We included 51 Alzheimer's disease‐spectrum (AD‐s), 38 LBD with cognitive impairment (LB‐abnlCog), 65 LBD with no cognitive impairment (LB‐nlCog), and 146 Controls. Pairwise between‐group comparisons examined the impact of diagnosis on number of illusory responses. Ordinal regression analysis compared the number of illusory responses on the Noise Pareidolia Task across diagnosis groups, adjusting for age, sex, and education. Analyses were repeated after removing participants with reported hallucinations or delusions. Result: See Table 1 for diagnosis group demographic characteristics. LB‐abnlCog were more than 10 times more likely than Controls and about 4–5 times more likely than AD‐s and LB‐nlCog participants to endorse illusory responses. The probability of endorsing one or more illusory response was 61% in the LB‐abnlCog group, compared to 26% in AD‐s, 25% in LB‐nlCog and 12% in Control participants (Figure 1). In LBD participants without hallucinations or delusions, 52% of those with mild cognitive impairment and 67% with dementia endorsed at least one illusory response. Conclusion: Illusory responses are common in cognitively impaired LBD patients, including those without any reported psychosis. The Noise Pareidolia Task does not distinguish between Alzheimer's disease and Lewy body patients until there is measurable cognitive impairment in the LBD patients, suggesting that early, unobtrusive pareidolias might arise in conjunction with cognitive decline in LBD.